The Effect of Work Ethics and Motivation on the Job Performance of Ony Comp Employees Malang - Aini, Lilies Nur; Nurtjahjani, Fullchis; Dhakirah, Sanita (Economics and Business Solutions Journal, 2021)
The era of change that is increasingly advanced, encourages people to want to achieve a better life. This achievement is shown through the performance and achievements given at work. So it takes the ability or performance of better employees. In fostering work skills and improving the performance of each employee, inseparable from the work ethic that is believed to be and the motivation possessed by individuals. The purpose of this study is to analyze the effects of work ethics and motivation on employee performance partially or simultaneously. The population in this study were employees of Ony Comp Malang who assessed 25 people. This study used a saturated sample technique and data analysis using multiple linear regression analysis.